2011
DOI: 10.1108/03684921111118004
|View full text |Cite
|
Sign up to set email alerts
|

Elementary sub‐atomic particles: the earliest adaptive systems

Abstract: Purpose -This paper considers a perspective on particulate matter as being formed from closed loops of waveform energy flow, consistent with observations by de Broglie, Schrödinger and others and supported by recent research findings. It demonstrates that all experimentally verified findings of special relativity may be derived directly from such a model. It further shows a clear form of auto-adaptive behaviour exhibited by such structures. Design/methodology/approach -A generalised closed-loop energy flow mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 38 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…(Hence the application of the factor c to all time elements in relativistic calculationstime literally travels at the speed of light.) As shown by Blackwell (2011), this perspective on time and matter explains, and provides full mathematical derivations of, all experimentally verified findings of special relativity.…”
Section: Space Time and Spacetimementioning
confidence: 90%
See 4 more Smart Citations
“…(Hence the application of the factor c to all time elements in relativistic calculationstime literally travels at the speed of light.) As shown by Blackwell (2011), this perspective on time and matter explains, and provides full mathematical derivations of, all experimentally verified findings of special relativity.…”
Section: Space Time and Spacetimementioning
confidence: 90%
“…This is clearly indicative of a cyclic component in Cosmic system dynamics the fundamental structure of an electron (Huang, 1952;Barut and Bracken, 1981;Hestenes, 1990). (3) Theoretical research has shown that a cyclic-photon model of particulate matter accounts for various quantum characteristics of an electron (Williamson and van der Mark, 1997) as well as providing a basis for all verifiable tenets of special relativity (Blackwell, 2011).…”
Section: Electric Chargementioning
confidence: 98%
See 3 more Smart Citations